2016
DOI: 10.1017/s1755048316000420
|View full text |Cite
|
Sign up to set email alerts
|

Faith and the Free Market: Evangelicals, the Tea Party, and Economic Attitudes

Abstract: We argue that concerted efforts by Tea Party leaders, Republican politicians, and leading Christian Right figures to establish and promote a connection between Christian faith and the free-market system has helped shift the economic attitudes of white evangelical Protestants in a more conservative direction. Our analysis of Public Religion Research Institute survey data finds that white evangelical Protestants express greater skepticism about an active role of government in society and believe economic growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Our findings thus are in line with Swartz's (2012) (Bean 2014a;2014b) and it is also not present among the evangelicals we studied. Consequently, the growing conservatism among American evangelicals in both the cultural and especially the economic domain, that was recently documented by Deckman et al (2016), may be more typical for the United States and may indeed by the result of the growing polarization in American politics between the Democratic and the Republican Party and of the emergence of the Tea Party, as Deckman et al suggest. In contrast, in the politically plural context of the Netherlands, where such a strong polarization between two political parties does not exist and partisanship is traditionally low (Scheepers, Peters, and Felling 2000) and has persisted to be low also after the turn of the century (Linssen et al 2014), partisan leanings may be less influential on the political attitudes of the electorate and the conservatism of Dutch evangelicals may, therefore, be confined to those moral issues where religion traditionally matters most: i.e., pro-life and homosexuality.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Our findings thus are in line with Swartz's (2012) (Bean 2014a;2014b) and it is also not present among the evangelicals we studied. Consequently, the growing conservatism among American evangelicals in both the cultural and especially the economic domain, that was recently documented by Deckman et al (2016), may be more typical for the United States and may indeed by the result of the growing polarization in American politics between the Democratic and the Republican Party and of the emergence of the Tea Party, as Deckman et al suggest. In contrast, in the politically plural context of the Netherlands, where such a strong polarization between two political parties does not exist and partisanship is traditionally low (Scheepers, Peters, and Felling 2000) and has persisted to be low also after the turn of the century (Linssen et al 2014), partisan leanings may be less influential on the political attitudes of the electorate and the conservatism of Dutch evangelicals may, therefore, be confined to those moral issues where religion traditionally matters most: i.e., pro-life and homosexuality.…”
Section: Resultsmentioning
confidence: 97%
“…However, this socio-economic inequality is considered to be an inevitable by-product of economic growth and thus a conservative position in the economic domain is also accompanied by a critical stance toward the provision of social services to alleviate poverty as well as by a critical view on the government's responsibility to reduce income differences (Felling and Peters 1986; cf. also, Deckman et al 2016). Within the cultural domain, in contrast, conservatism relates to moral conservatism and actually boils down to support for the restriction of individual freedom.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 85%
See 2 more Smart Citations
“…The literature on morality politics shows that members of Congress tend to treat these types of issues differently (Koopman ; Oldmixon ), but studies of the effect of religion on mass political attitudes has produced conflicting results. Layman and Green () find that the effect of religion on policy attitudes is mostly confined to narrow policy contexts, but other researchers have found that religious worldviews influence attitudes on economics (Barker and Carman ; Deckman et al ) and foreign policy (Barker, Hurwitz, and Nelson ). A multivariate analysis of ideological scores in the three different issue areas (social, economic, and foreign) shows that evangelicals are significantly more conservative than nonevangelicals on all three dimensions, but the effect of religion is greatest on the social dimension.…”
mentioning
confidence: 99%